UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI METODE PEMBELAJARAN WORD SQUARE PADA SISWA KELAS VI SD NEGERI 163087 TEBING TINGGI - Syahrial Nasty (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2020)
The types of this research is classroom action research, there are 2 cycles in this research with four phases: planning, implementation, observation, reflection.The locaton of this research at SDN 163087 Tebing Tinggi. This research aim to describe this increase in teacher activity, student activity, and improvement of student learning result in social studies by appliying Word Square learning method. The subject of research is teacher and student third grader which amounted to 32 students. This study used a qualitative descriptive analysis technique. The result obtained from the learning results in the first cycle is 75% has increased in two cycle get 90,62 %  and students activity in cycle I is 77, 4% has increased in cycle II get 81,2%. From the data obtained can be concluded that the word square learning model can improve students learning outcomes in class VI SDN 163087 Tebing Tinggi. Keywords: Word Square, IPS, Qualitative Descriptive